Caveolae and caveolins role in health and disease - R. I. Voroblev; G. I. Shumakher; M. A. Khoreva; I. V. Osipova; Yu. V. Korenovsky (Кардиоваскулярная терапия и профилактика, 2008)
Discovered more than 50 years ago, caveolae for a long time have remained enigmatic plasmalemmal organelles. They were described as 50-100-nm invaginations of the plasma membrane observed using electron microscopy. Later, caveolins were identified - the proteins acting as principal structural components of caveolae membrane. Since then, the important role of caveolins in a variety of cellular functions, including endocytosis processes, lipid homeostasis, signal transduction, and tumor suppression, has been demonstrated in numerous studies. In caveolin-deficient mice, the cellular functions of caveolae and caveolins could be studied, with the results extrapolated to human physiology area. The evidence is accumulating on caveolins' role in the pathogenesis of human disease, including cancer, muscular dystrophy, and type II diabetes. In this review, the role of caveolae and caveolins in health and disease is described.